Penyuluhan dan Edukasi tentang Kelembagaan pada Proses Pengelolaan Limbah Kotoran Hewan bagi Anggota Koperasi Serba Usaha Karya Nugraha Jaya (KSU KKS) di Kelurahan Cipari Kecamatan Cigugur - Muliawaty, Lia; Ruyani, Nyi Raden (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This community service program (PKM) addresses the suboptimal management of dairy cattle manure (kohe) in Cipari Village, Cigugur District, Kuningan Regency, despite its significant dairy cattle population (approximately 8,000 head) and supportive local government policies. Unmanaged kohe leads to environmental pollution, foul odors, and disease vectors, causing community complaints. Many livestock farmers lack effective waste management systems like composting or biogas. This PKM aims to bridge the gap between existing strong local policies and their on-the-ground implementation, by focusing on